Kinetic study of low-temperature CO2 plasmas under non-equilibrium conditions. I. Relaxation of vibrational energy. (29th January 2018) - Silva, T; Grofulović, M; Klarenaar, B L M; Morillo-Candas, A S; Guaitella, O; Engeln, R; Pintassilgo, C D; Guerra, V
Abstract: A kinetic model describing the time evolution of ∼70 individual CO2 (X1 Σ + ) vibrational levels during the afterglow of a pulsed DC glow discharge is developed in order to contribute to the understanding of vibrational energy transfer in CO2 plasmas. The results of the simulations are compared against in situ Fourier transform infrared spectroscopy data obtained in a pulsed DC glow discharge and its afterglow at pressures of a few Torr and discharge currents of around 50 mA. The very good agreement between the model predictions and the experimental results validates the kinetic scheme considered here and the corresponding vibration–vibration and vibration–translation rate coefficients. In this sense, it establishes a reaction mechanism for the vibrational kinetics of these CO2 energy levels and offers a firm basis to understand the vibrational relaxation in CO2 plasmas. It is shown that first-order perturbation theories, namely, the Schwartz–Slawsky–Herzfeld and Sharma–Brau methods, provide a good description of CO2 vibrations under low excitation regimes.